Relics of the Unseen Presence? Evocations of Native American Indian Heritage and Western-Hero Road Poems in Bruce Baillie’s Mass for the Dakota Sioux and Quixote - Boczkowska, Kornelia (Studia Anglica Posnaniensia, 2018)
In this paper I discuss the ways in which Bruce Baillie’s Mass for the Dakota Sioux (1964) and Quixote (1965) evoke Native American Indian heritage and western-hero road poems by challenging the concept of the American landscape and incorporating conventions traditionally associated with cinéma pur, cinéma vérité, and the city symphony. Both pictures, seen as largely ambiguous and ironic travelogue forms, expose their audiences to “the sheer beauty of the phenomenal world” (Sitney 2002: 182) and nurture nostalgic feelings for the lost indigenous civilizations, while simultaneously reinforcing the image of an American conquistador, hence creating a strong sense of dialectical tension. Moreover, albeit differing in a specific use of imagery and editing, the films rely on dense, collage-like and often superimposed images, which clearly contribute to the complexity of mood conveyed on screen and emphasize the striking conceptual contrast between white American and Indian culture. Taking such an assumption, I argue that although frequently referred to as epic road poems obliquely critical of the U.S. westward expansion and manifest destiny, the analyzed works’ use of plot reduction, observational and documentary style as well as kinaesthetic visual modes and rhythmic editing derive primarily from the cinéma pur’s camerawork, the cinéma vérité’s superstructure, and the city symphony’s spatial arrangement of urban environments. Such multifaceted inspirations do not only diversify Mass’ and Quixote’s non-narrative aesthetics, but also help document an intriguing psychogeography of the 1960s American landscapes, thus making a valuable contribution to the history of experimental filmmaking dealing with Native American Indian heritage.